Prevalence of coronary anomalies detected by computed tomography at the Instituto Nacional Cardiovascular- INCOR - Rodríguez Urteaga, Zoila I. (2022)
Objective: To determine the prevalence of coronary anomalies (CA) in patients evaluated by 64-detector computed tomography (CT) at the Instituto Nacional Cardiovascular in Peru between 2016 and 2020. Materials and methods: Retrospective observational study, coronary artery CT scans of 1486 patients were performed on a 64-detector row CT scanner and reviewed in search for coronary anomalies. Results: The prevalence of CA detected by CT was 4.71% (70 cases) of which 64.3% were male. Abnormalities of origin were the most frequent, of which the origin of a coronary artery from the opposite coronary sinus was the most common (48.6%), with the right coronary being the main anomalous artery (31%), and the main path was interarterial (31%). Anomalous origin of the left main coronary from the pulmonary artery was found in 5 patients. Among the anomalies of the intrinsic coronary arterial anatomy the most frequent was the double left anterior descending artery (10%). Coronary fistulas accounted for 11.4% of cases. Conclusions: The prevalence of CA detected by 64-detector CT in a Peruvian institute was 4.71%. The most frequent coronary anomaly was the origin of the right coronary artery from the left coronary sinus with interarterial trajectory.